Number Count of 2MRS Galaxies in the J, H, K Bands - Arbabi Bidgoli, S.; Rah, M.; Yousefi-Sostani, A.
The Copernican principle has been the motivation for the present study on the number density of galaxies. In this work we have carried out a number count of galaxies in the 2MRS catalog in the K, H and J bands. The results presented here have obtained on volume-limited samples with equal widths or redshift bins. The main result of this study is the number count of galaxies which have been plotted in concentric spherical shells with the observer at the center. The obtained result in the three bands show a similar behavior up to a distance of 1.7 × 102 Mpc and behave differently from there on.
Keywords: Astronomy